The evaluation of awareness, attitude, and performance of the residents of Bandar Abbas in relation to preventive behaviors and methods for controlling dengue fever - Laleh Hassani; Asiyeh Yari; Nahid Shahabi; Shokrollah Mohseni; Mehran Shahi (BMC Research Notes)
Abstract Objective Dengue fever is a rapidly spreading viral disease transmitted by mosquitoes, and it is becoming a global concern. This study aimed to assess the awareness, attitude, and performance of the people in Hormozgan province in carrying out preventive behaviors and dengue fever control methods. Method This descriptive-analytical study was conducted in 1401 in Bandar Abbas, Iran. A total of 642 men and women participated in the study, and a researcher-made questionnaire was used to collect data on demographic information, awareness, attitude, and performance. The data were analyzed using descriptive statistics. Findings The study included 642 citizens of Bandar Abbas, with the majority being male. The average scores for awareness, attitude, and performance were relatively low, indicating insufficient knowledge and weak preventive behaviors regarding dengue fever. Conclusion The findings suggest a need for educational programs to increase awareness and preventive behaviors among the citizens, especially in essential areas such as protected coverage against mosquito bites and inspection of water accumulation sites in homes. It is also important for health centers and mass media to provide more information and education about dengue fever and its prevention.